Advancing the design and delivery of CRISPR antimicrobials. (December 2017) - Fagen, Jennie R.; Collias, Daphne; Singh, Atul K.; Beisel, Chase L.
Abstract: CRISPR-Cas systems are prokaryotic immune systems whose RNA-guided nucleases have been co-opted for applications ranging from genome editing and gene regulation to in vitro diagnostics and DNA imaging. Here, we review the current efforts toward repurposing CRISPR nucleases as programmable antimicrobials. Antimicrobial activity is achieved by targeted cleavage of multidrug-resistance plasmids or the bacterial chromosome, resulting in antibiotic sensitivity or cell death. As part of the review, we discuss the different types of nucleases available for CRISPR antimicrobials, the use of bacteriophages as delivery vehicles, and opportunities to enhance antimicrobial activity, delivery, and specificity. Through further advances, these programmable DNA-targeting antimicrobials may help quell the spread of antimicrobial resistance and provide a tool for the manipulation of complex microbial communities. Graphical abstract: Image 1 Highlights: CRISPR-Cas immune systems can be harnessed as sequence-specific antibacterials. The different types of CRISPR nucleases offer distinct antimicrobial mechanisms. Engineered bacteriophage are primarily being used for CRISPR delivery. Advances are needed to prevent inefficient or off-target killing.